Pengaruh Intensitas Aset Tetap dan Likuiditas Terhadap Penghindaran Pajak pada Perusahaan Manufaktur - Naomi Jay Tazshiro; Ayunda Firzha Ekawati Kohongia; Olifia Mardiana; Agunstine Dwianika (Jurnal Akuntan Publik, 2023)
This research aims to clarify the description of an object to be researched, this type of quantitative research will determine the relationship between the variables being researched will be significant and produce conclusions with the aim of testing the hypothesis that has been set. The data source used in this study uses secondary data and data collection in this study is taken from the company's financial statements. The population used in this research is manufacturing companies in the goods & consumption industry sector and miscellaneous industries listed on the Indonesia Stock Exchange in 2017-2021, and the data sample is 75. From the data obtained, processed with Microsoft Excel and SPSS 29 software. The sampling technique in this study was carried out using purposive sampling method. The analysis method used in this research is multiple linear analysis method. The results of this study indicate that fixed asset intensity and liquidity have a significant effect on tax avoidance. This research is important for decision makers such as tax managers in ensuring that corporate tax planning goes well, as well as for the Directorate General of Taxes in implementing the best strategy to get tax revenue problems in Indonesia